Female Family Echelon and Capital Structure Decisions in Family Firm - Hadi Sumarsono (Universitas Muhammadiyah Surakarta, 2022)
This research aims to examine how female family echelons (the presence female family on commisioner or director) effect on leverage. Sample use in research are 1374 firms years observation from nonbank and nonfinancial sector actived trade on Indonesia Stock Exchange over 2011 to 2015. Using regression of fixed effect model, this finding suggest that family firm are less leverage than nonfamily firm. Proportion of family ownership, family commisioner and family director insignificant affect on leverage, however, relationship between family ownership and leverage are significantly nonlinear (U-shape). Female family echelons effect on leverage. Family firms more risk averse than nonfamily firm due to involvement women on family echelons.